#1.
![x^2 + 3x - 18 = 0 x^2 + 3x - 18 = 0](https://tex.z-dn.net/?f=x%5E2%20%2B%203x%20-%2018%20%3D%200)
По теореме Виета:
![x_1 = 3; x_2 = -6 x_1 = 3; x_2 = -6](https://tex.z-dn.net/?f=x_1%20%3D%203%3B%20x_2%20%3D%20-6)
Ответ: -63.
#2.
![x^2 = -13x - 36\\x^2 + 13x + 36 = 0 x^2 = -13x - 36\\x^2 + 13x + 36 = 0](https://tex.z-dn.net/?f=x%5E2%20%3D%20-13x%20-%2036%5C%5Cx%5E2%20%2B%2013x%20%2B%2036%20%3D%200)
По теореме Виета:
![x_1 = -9; x_2 = -4 x_1 = -9; x_2 = -4](https://tex.z-dn.net/?f=x_1%20%3D%20-9%3B%20x_2%20%3D%20-4)
Ответ: -4.
#3.
![16x^2 - 1 = 0\\16x^2 = 1\\x^2 = \frac{1}{16} \\\\x_1 = \frac{1}{4}; x_2 = - \frac{1}{4} 16x^2 - 1 = 0\\16x^2 = 1\\x^2 = \frac{1}{16} \\\\x_1 = \frac{1}{4}; x_2 = - \frac{1}{4}](https://tex.z-dn.net/?f=16x%5E2%20-%201%20%3D%200%5C%5C16x%5E2%20%3D%201%5C%5Cx%5E2%20%3D%20%5Cfrac%7B1%7D%7B16%7D%20%5C%5C%5C%5Cx_1%20%3D%20%5Cfrac%7B1%7D%7B4%7D%3B%20x_2%20%3D%20-%20%5Cfrac%7B1%7D%7B4%7D)
Ответ:
.
#4.
![3x^2 -9x = 0\\3x(x - 3) = 0\\\left[\begin{array}{ccc}3x = 0\\x-3 = 0\end{array}\right\\\\x_1 = 0; x_2 = 3 3x^2 -9x = 0\\3x(x - 3) = 0\\\left[\begin{array}{ccc}3x = 0\\x-3 = 0\end{array}\right\\\\x_1 = 0; x_2 = 3](https://tex.z-dn.net/?f=3x%5E2%20-9x%20%3D%200%5C%5C3x%28x%20-%203%29%20%3D%200%5C%5C%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D3x%20%3D%200%5C%5Cx-3%20%3D%200%5Cend%7Barray%7D%5Cright%5C%5C%5C%5Cx_1%20%3D%200%3B%20x_2%20%3D%203)
Ответ: 03.
#5.
![x^2 - 2x - 35 = 0 x^2 - 2x - 35 = 0](https://tex.z-dn.net/?f=x%5E2%20-%202x%20-%2035%20%3D%200)
По теореме Виета:
![x_1 = 7; x_2 = -5 x_1 = 7; x_2 = -5](https://tex.z-dn.net/?f=x_1%20%3D%207%3B%20x_2%20%3D%20-5)
Ответ: -57.
#6.
![x^2 +px + q = 0;\\x_1 = -4; x_2 = -1; \\x_2 + 5 + 4 = 0\\q = 4 x^2 +px + q = 0;\\x_1 = -4; x_2 = -1; \\x_2 + 5 + 4 = 0\\q = 4](https://tex.z-dn.net/?f=x%5E2%20%2Bpx%20%2B%20q%20%3D%200%3B%5C%5Cx_1%20%3D%20-4%3B%20x_2%20%3D%20-1%3B%20%5C%5Cx_2%20%2B%205%20%2B%204%20%3D%200%5C%5Cq%20%3D%204)
Ответ: 4.
#7.
![x^2 + 5x - 24 = (x+8)(x-a) x^2 + 5x - 24 = (x+8)(x-a)](https://tex.z-dn.net/?f=x%5E2%20%2B%205x%20-%2024%20%3D%20%28x%2B8%29%28x-a%29)
По формуле -
найдём переменную a, которая будет являться вторым корнем:
![x^2 + 5x - 24 = 0 x^2 + 5x - 24 = 0](https://tex.z-dn.net/?f=x%5E2%20%2B%205x%20-%2024%20%3D%200)
По теореме Виета:
![x_1 = -8; x_2 = 3 x_1 = -8; x_2 = 3](https://tex.z-dn.net/?f=x_1%20%3D%20-8%3B%20x_2%20%3D%203)
a = 3
Ответ: 3.
#8.
![x^2 - 9x + 20 = (x - 5)(x-a)\\x^2 - 9x + 20 = 0 x^2 - 9x + 20 = (x - 5)(x-a)\\x^2 - 9x + 20 = 0](https://tex.z-dn.net/?f=x%5E2%20-%209x%20%2B%2020%20%3D%20%28x%20-%205%29%28x-a%29%5C%5Cx%5E2%20-%209x%20%2B%2020%20%3D%200)
По теореме Виета:
![x_1 = 5; x_2 = 4 x_1 = 5; x_2 = 4](https://tex.z-dn.net/?f=x_1%20%3D%205%3B%20x_2%20%3D%204)
a = 4
Ответ: 4.
#9.
![(x-6)^2 + (x+8)^2 = 2x^2\\x^2 - 12x + 36 + x^2 + 16x + 64 = 2x^2\\2x^2 - 2x^2 + 16x - 12x + 36 + 64 = 0\\4x = -100\\x = -25 (x-6)^2 + (x+8)^2 = 2x^2\\x^2 - 12x + 36 + x^2 + 16x + 64 = 2x^2\\2x^2 - 2x^2 + 16x - 12x + 36 + 64 = 0\\4x = -100\\x = -25](https://tex.z-dn.net/?f=%28x-6%29%5E2%20%2B%20%28x%2B8%29%5E2%20%3D%202x%5E2%5C%5Cx%5E2%20-%2012x%20%2B%2036%20%2B%20x%5E2%20%2B%2016x%20%2B%2064%20%3D%202x%5E2%5C%5C2x%5E2%20-%202x%5E2%20%2B%2016x%20-%2012x%20%2B%2036%20%2B%2064%20%3D%200%5C%5C4x%20%3D%20-100%5C%5Cx%20%3D%20-25)
Ответ: -25.
#10.
![x^2 + x + 6 = -x^2 - 3x + (-2 + 2x^2)\\x^2 + x + 6 = - x^2 - 3x - 2 + 2x^2\\x^2 +x + 6 = x^2 - 3x - 2\\x^2 - x^2 + x + 3x = -2 - 6\\4x = -8\\x = -2 x^2 + x + 6 = -x^2 - 3x + (-2 + 2x^2)\\x^2 + x + 6 = - x^2 - 3x - 2 + 2x^2\\x^2 +x + 6 = x^2 - 3x - 2\\x^2 - x^2 + x + 3x = -2 - 6\\4x = -8\\x = -2](https://tex.z-dn.net/?f=x%5E2%20%2B%20x%20%2B%206%20%3D%20-x%5E2%20-%203x%20%2B%20%28-2%20%2B%202x%5E2%29%5C%5Cx%5E2%20%2B%20x%20%2B%206%20%3D%20-%20x%5E2%20-%203x%20-%202%20%2B%202x%5E2%5C%5Cx%5E2%20%2Bx%20%2B%206%20%3D%20x%5E2%20-%203x%20-%202%5C%5Cx%5E2%20-%20x%5E2%20%2B%20x%20%2B%203x%20%3D%20-2%20-%206%5C%5C4x%20%3D%20-8%5C%5Cx%20%3D%20-2)
Ответ: -2.
#11.
![(x+1)^2 = (2-x)^2 \\x^2 + 2x + 1 = 4 - 4x + x^2\\6x = 3\\x = 2 (x+1)^2 = (2-x)^2 \\x^2 + 2x + 1 = 4 - 4x + x^2\\6x = 3\\x = 2](https://tex.z-dn.net/?f=%28x%2B1%29%5E2%20%3D%20%282-x%29%5E2%20%5C%5Cx%5E2%20%2B%202x%20%2B%201%20%3D%204%20-%204x%20%2B%20x%5E2%5C%5C6x%20%3D%203%5C%5Cx%20%3D%202)
Ответ: 2.
#12.
![(x+10)(-x-8) = 0\\\\\left[\begin{array}{ccc}x + 10 = 0\\-x - 8 = 0\end{array}\right\\\\\left[\begin{array}{ccc}x = -10\\x = -8\end{array}\right (x+10)(-x-8) = 0\\\\\left[\begin{array}{ccc}x + 10 = 0\\-x - 8 = 0\end{array}\right\\\\\left[\begin{array}{ccc}x = -10\\x = -8\end{array}\right](https://tex.z-dn.net/?f=%28x%2B10%29%28-x-8%29%20%3D%200%5C%5C%5C%5C%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7Dx%20%2B%2010%20%3D%200%5C%5C-x%20-%208%20%3D%200%5Cend%7Barray%7D%5Cright%5C%5C%5C%5C%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7Dx%20%3D%20-10%5C%5Cx%20%20%3D%20-8%5Cend%7Barray%7D%5Cright)
Ответ: -8.
#13.
![(5x+2)(x-6) = 0\\\\\left[\begin{array}{ccc}5x + 2 = 0\\x - 6 = 0\end{array}\right\\\\\left[\begin{array}{ccc}x = -0,4\\x = 6\end{array}\right (5x+2)(x-6) = 0\\\\\left[\begin{array}{ccc}5x + 2 = 0\\x - 6 = 0\end{array}\right\\\\\left[\begin{array}{ccc}x = -0,4\\x = 6\end{array}\right](https://tex.z-dn.net/?f=%285x%2B2%29%28x-6%29%20%3D%200%5C%5C%5C%5C%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D5x%20%2B%202%20%3D%200%5C%5Cx%20-%206%20%3D%200%5Cend%7Barray%7D%5Cright%5C%5C%5C%5C%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7Dx%20%3D%20-0%2C4%5C%5Cx%20%20%3D%206%5Cend%7Barray%7D%5Cright)
Ответ: -0,4.
#14.
![5x^2 + 8x + 3 = 0\\D = 64 - 15 * 4 = 4 = 2^2\\x_1 = (-8 + 2) : 10 = -0,6\\x_2 = (-8 - 2) : 10 = -1 5x^2 + 8x + 3 = 0\\D = 64 - 15 * 4 = 4 = 2^2\\x_1 = (-8 + 2) : 10 = -0,6\\x_2 = (-8 - 2) : 10 = -1](https://tex.z-dn.net/?f=5x%5E2%20%2B%208x%20%2B%203%20%3D%200%5C%5CD%20%3D%2064%20-%2015%20%2A%204%20%3D%204%20%3D%202%5E2%5C%5Cx_1%20%3D%20%28-8%20%2B%202%29%20%3A%2010%20%3D%20-0%2C6%5C%5Cx_2%20%3D%20%28-8%20-%202%29%20%3A%2010%20%3D%20-1)
Ответ: -0,6.
#15.
![\frac{4}{3} x^2 + 4x + 3 = 0\\D = 16 - 12 * \frac{4}{3} = 16 - 4*4 = 0\\\\x = -4 : (\frac{8}{3} ) = \frac{-4 * 3}{8} = -1,5 \frac{4}{3} x^2 + 4x + 3 = 0\\D = 16 - 12 * \frac{4}{3} = 16 - 4*4 = 0\\\\x = -4 : (\frac{8}{3} ) = \frac{-4 * 3}{8} = -1,5](https://tex.z-dn.net/?f=%5Cfrac%7B4%7D%7B3%7D%20x%5E2%20%2B%204x%20%2B%203%20%3D%200%5C%5CD%20%3D%2016%20-%2012%20%2A%20%5Cfrac%7B4%7D%7B3%7D%20%3D%2016%20-%204%2A4%20%3D%200%5C%5C%5C%5Cx%20%3D%20-4%20%3A%20%28%5Cfrac%7B8%7D%7B3%7D%20%29%20%3D%20%5Cfrac%7B-4%20%2A%203%7D%7B8%7D%20%3D%20-1%2C5)
Ответ: -1,5.